Siknure let me live - Watkins, Jonathan 1957- (Ikon Gallery, 2022)
Mayunkiki is an Ainu artist and musician. This book accompanies the first solo exhibition by an Ainu artist in the UK.0Includes an essay by Jonathan Watkins and an in-conversation text between Asami Hosokawa, Hirohisa Asahara and Mayunkiki.00About the artist and exhibition:00Born in Asahikawa, on the island of Hokkaid? in Japan, Mayunkiki?s artistic practice arises from her Indigenous identity.0Through a variety of works, this exhibition conveys the predicament of her community in recent times.0Like many Indigenous people, the Ainu have suffered systematic marginalisation by a central government and Mayunkiki is especially concerned to raise the profile of their traditional culture, including Sinuye (traditional tattooing practice for Ainu women, banned by the Hokkaid? Development Commission and not yet fully lifted) and Upopo (traditional Ainu music rooted in rhythmic patterns and singing in a trance-like chorus).00Exhibition: Ikon Gallery, Birmingham, UK (09.09. - 13.11.2022)
Keywords: Mayunkiki -- 1980-; Mayunkiki / Exhibitions; Art, Ainu / Exhibitions; Bildband; Ausstellungskatalog -- Ikon Gallery -- 09.09.2022-13.11.2022 -- Birmingham; Gespräch